Aktivitas Komunikasi Kelompok dalam Tradisi Lelang Pesta Pernikahan Adat Desa Kalampadu Kecamatan Muara Kuang Kabupaten Ogan Ilir - Rukmana Sari; Choiriyah Choiriyah; Manalullaili Manalullaili (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2018)
Group communication as face-to-face interaction of three or more individuals in order to obtain the desired intent or purpose such as a variety of information, self-maintenance or problem solving so that all members can grow the personal characteristics of other members accurately. Tradition is something that has been done for a long time and becomes part of the life of a community group, usually from a country, culture, time, or religion. This thesis is entitled